SURABAYA FRISHAPP: KOTA TERAPUNG MASA DEPAN DENGAN DESAIN âFLOATING RING SHAPED PLATEâ - Wiyono, Puput; Putra, Rigan Satria Asmara; Pratiwi, Titis Wahyu (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
Based on data collected by Indonesian Maritime Magazine, in year 2030 Indonesia will lose about 2,000 islands due to global warming. While the average rate of population growth in Indonesia reaches 6% per year, this results in the amount of land to be used also diminishing. Therefore we need a solution that can overcome these problems. Reclamation is often the answer to these problems. Yet, it results in damage to the marine ecosystem. Surabaya Frishapp a floating city concept that uses the concept of "floating ring shaped plate". The city is designed with a capacity of 36,000 people, which is more than enough to accommodate the residents of a city. The city uses a system structure that allows components fluctuate city following the sea level. Various synergic attempts with natural environment are proposed in almost all the cities so that the destruction of marine systems and avoid any further natural.